2017
DOI: 10.1038/cddis.2017.504
|View full text |Cite
|
Sign up to set email alerts
|

Current progress in the derivation and therapeutic application of neural stem cells

Abstract: Neural stem cells (NSCs) have a unique role in neural regeneration. Cell therapy based on NSC transplantation is a promising tool for the treatment of nervous system diseases. However, there are still many issues and controversies associated with the derivation and therapeutic application of these cells. In this review, we summarize the different sources of NSCs and their derivation methods, including direct isolation from primary tissues, differentiation from pluripotent stem cells and transdifferentiation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
111
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 127 publications
0
111
0
Order By: Relevance
“…Similar to their ex vivo counterparts, iNSCs are multipotent stem cells giving rise to neurons and glial cells [71,76,77]. However, the differentiation potential can vary depending on the iNSC population, as well as the in vitro differentiation protocol used (e.g., spontaneous, undirected, and directed in vitro differentiation approaches) ( Table 2).…”
Section: Differentiation Potential Of Inscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to their ex vivo counterparts, iNSCs are multipotent stem cells giving rise to neurons and glial cells [71,76,77]. However, the differentiation potential can vary depending on the iNSC population, as well as the in vitro differentiation protocol used (e.g., spontaneous, undirected, and directed in vitro differentiation approaches) ( Table 2).…”
Section: Differentiation Potential Of Inscsmentioning
confidence: 99%
“…It might well be that in both studies, the brains were analyzed too early, given the fact that oligodendrocytic cells arise later than neurons and astrocytes during neurodevelopment [75]. This might be due to the transplantation of iNSCs into subventricular zones, one of the stem cell niches of the adult brain, or the fact that mouse NSCs differentiate more rapidly than human NSCs [71,76]. On the other hand, Han et al transplanted mouse iNSCs into the subventricular zones of adult mice.…”
Section: Differentiation Potential Of Inscsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the growth areas of greatest impact in clinical research is in the use of cell therapies; the use of living cells to repair, replace and augment the existing body tissues [1]. This can take the form of neural stem cells selected to replace missing or damaged tissue in Alzheimer's or Parkinson's disease [2]; or it can be used to treat disease by modifying specific cells, such as the use of lentivirus-augmented T lymphocytes for CAR-T therapies, where altered immune cells are used to combat cancer by reprogramming them [3]. As the interest in cellular therapeutics grow, so does the need for isolating cells of therapeutic importance.…”
Section: Separation and Expansion Technologies The Need For Label-frementioning
confidence: 99%
“…Pioneering studies over 40 years ago revealed that human neurons could be transplanted into rodent brains (Stenevi et al, 1976), but the limited supply of neurons led most studies to focus on replacement of degenerating cell types rather than on monitoring basic aspects of human neuronal development (Tang et al, 2017). However, the generation of human-induced pluripotent stem cells (iPSCs) now provides an unlimited supply of human neuronal cells across normal and disease genotypes (Ferreira and Mostajo-Radji, 2013), and cerebral orga-noids further enable the study of 3D neuronal interactions in vitro (Pașca, 2018).…”
mentioning
confidence: 99%